In Other Rooms, Other Wonders - Daniyal Mueenuddin (Haryana, India Random House Publishers India (Pvt.) Ltd., 2015)
Each compelling tale revolves around the life and legacy of K.K. Harouni, a wealthy landowner in feudal, corruption-fueled Lahore. In this cutthroat society, a servant girl can immediately gain prestige by seducing a powerful married man--and then lose it just as swiftly.
In Other Rooms, Other Wonders illuminates a place and people as it describes the overlapping worlds of an extended Pakistani landowning family. Servants, masters, peasants and socialites, all inextricably bound to each other, confront the advantages and constraints of their station, the dissolution of old ways, and the shock of change. These richly textured stories reveal the complexities of Pakistani class and culture, as they describe the loves, triumphs, misunderstandings and tragedies of everyday life.
Keywords: Pakistan -- Social conditions -- Social classes -- Manners and customs